Exercise Training Adds Cardiometabolic Benefits of a Paleolithic Diet in Type 2 Diabetes Mellitus. Issue 2 (22nd January 2019) - Otten, Julia; Andersson, Jonas; Ståhl, Jens; Stomby, Andreas; Saleh, Ahmed; Waling, Maria; Ryberg, Mats; Hauksson, Jon; Svensson, Michael; Johansson, Bengt; Olsson, Tommy
Abstract : Background: The accumulation of myocardial triglycerides and remodeling of the left ventricle are common features in type 2 diabetes mellitus and represent potential risk factors for the development of diastolic and systolic dysfunction. A few studies have investigated the separate effects of diet and exercise training on cardiac function, but none have investigated myocardial changes in response to a combined diet and exercise intervention. This 12‐week randomized study assessed the effects of a Paleolithic diet, with and without additional supervised exercise training, on cardiac fat, structure, and function. Methods and Results: Twenty‐two overweight and obese subjects with type 2 diabetes mellitus were randomized to either a Paleolithic diet and standard‐care exercise recommendations (PD) or to a Paleolithic diet plus supervised exercise training 3 hours per week (PD‐EX). This study includes secondary end points related to cardiac structure and function, ie, myocardial triglycerides levels, cardiac morphology, and strain were measured using cardiovascular magnetic resonance, including proton spectroscopy, at baseline and after 12 weeks. Both groups showed major favorable metabolic changes. The PD‐EX group showed significant decreases in myocardial triglycerides levels (−45%, P =0.038) and left ventricle mass to end‐diastolic volume ratio (−13%, P =0.008) while the left ventricle end‐diastolic volume and stroke volume increased significantly (+14%, P =0.004 and +17%, P =0.008, respectively). These variables were unchanged in the PD group. Conclusions: Exercise training plus a Paleolithic diet reduced myocardial triglycerides levels and improved left ventricle remodeling in overweight/obese subjects with type 2 diabetes mellitus. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01513798.